Mitigating Risks in Hospital Facilities—An Analysis of the Relationship Between Healthcare Risks and the Built Environment: A Literature Review and Survey in the Italian Scenario - Beatrice Pattaro; Michele Dolcini; Andrea Brambilla; Stefano Capolongo (Hygiene)
Background: This study examines the role of the built environment in mitigating risk in healthcare facilities, with a particular focus on how the design of hospital infrastructures can influence and improve the safety of patients, staff, and visitors. Methods: A two-phase mixed-methods approach was adopted. First, a scoping literature review was conducted to identify design-based strategies targeting five categories of risk: healthcare-associated infections (HAIs), indoor air quality (IAQ), safety, falls, and emergency resilience. Based on this review, a structured questionnaire was developed and administered to a sample of hospital facilities in Northern Italy to assess the implementation of the strategies emerged. Results: The literature review identifies recurring specific design solutions and strategies that have proven effective in mitigating risks in healthcare infrastructures in the following dimensions: infection mitigation, indoor air quality, falls reduction, safety, emergency preparedness. At the same time, survey data from (n = 9) hospitals indicate a significant implementation gap. Key shortcomings included a lack of spatial flexibility, limited environmental monitoring (especially for IAQ and acoustic conditions), and underutilization of antibacterial surfaces. Antibacterial flooring and wall finishes were absent in (n = 4/9) and (n = 6/9) of the facilities, respectively. IAQ monitoring was mostly confined to surgical areas, with (n = 0/9) facility reporting comprehensive building-wide monitoring. Only two (n = 2) facilities reported adaptable spaces suitable for emergency conversion and accessible green areas. Conclusions: This study provides a comprehensive overview of risk mitigation strategies in hospital design. The results reveal critical gaps in implementation, particularly in spatial flexibility, environmental monitoring, and antimicrobial surfaces. Future research should focus on developing adaptable design models that are context-sensitive, scalable, and capable of enhancing healthcare resilience in response to emerging global health threats.